Humans-with-Media and the Reorganization of Mathematical Thinking - Borba, Marcelo C. author. aut Link
XXII, 232 p.
Keywords: This book offers a new conceptual framework for reflecting on the role of information and communication technology in mathematics education. Borba and Villarreal provide examples from research conducted at the level of basic and university-level education, developed by their research group based in Brazil, and discuss their findings in the light of the relevant literature. Arguing that different media reorganize mathematical thinking in different ways, they discuss how computers, writing and oral discourse transform education at an epistemological as well as a political level. Modeling and experimentation are seen as pedagogical approaches which are in harmony with changes brought about by the presence of information and communication technology in educational settings. Examples of research about on-line mathematics education courses, and Internet used in regular mathematics courses, are presented and discussed at a theoretical level. In this book, mathematical knowledge is seen as developed by collectives of humans-with-media. The authors propose that knowledge is never constructed solely by humans, but by collectives of humans and technologies of intelligence. Theoretical discussion developed in the book, together with new examples, shed new light on discussions regarding visualization, experimentation and multiple representations in mathematics education. Insightful examples from educational practice open up new paths for the reader.